EVALUATION OF FUTSALL DEVELOPMENT PROGRAM AT CLUB RAFHELY FC KURANJI DISTRICT PADANG CITY - Ramisdo Febri; Anton Komaini (JURNAL STAMINA, 2019)
The problem in this study is the lack of knowledge about the evaluation of futsall development at Club Rafhely FC Kuranji district in Padang city. The purpose of this study was to examine the evaluation of futsall development at Club Rafhely FC Kuranji district in Padang city. The type of research used is qualitative research. The informants in this study were Trustees / Owners, coach and Athletes in Club Rafhely FC Kuranji district in Padang city., amounting to 3 people, consisting of 1 trustees / owner, 1 coach and 1 athlete. The instrument used in this study is an interview then supported by documentation. The technique of collecting data in this research uses the CIPP method (context, input, process and product). Based on the results of research on the evaluation of Club Rafhely FC program in Kuranji District, Padang City with context, input, process and product indicators, it can be concluded that:1) Context, the coaching program runs well, but there is no coaching at an early age, management and funding training programs run well and smoothly, as well as adequate and national standard facilities and infrastructure, 2) Input, AFC licensed trainers and 18 athletes who were obtained from the talent search and selection process, 3) Process, training program as planned by the coach ,. However, not a few athletes who do not understand the exercise program that is applied. So, evaluation is needed after training to find out the obstacles in the training program, which will then be held to focus on overcoming obstacles in coaching. 4) Product, achievement at the regional level is classified as very good. However, for the national level it must be improved and for the management performance it has run well.